Analyzing public policy effectiveness in enhancing accountability and transparency in service quality - Andi Rasyid Pananrangi; Imran ismail; Delly Mustafa; Askar Askar; A Rizal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Public policy serves as a framework to address public needs and interests, including the regulation of community services. Recognizing the critical importance of public services, governments are motivated to improve service quality through effective public policy implementation. This study aims to analyze the role of public policies in enhancing specific aspects of service quality, such as transparency, accountability, and professionalism. Using qualitative research methods, this study employs a literature study approach with a systematic selection of relevant sources, including peer-reviewed journals, government reports, and policy documents. Data analysis follows three stages: data reduction, data presentation, and conclusion drawing, ensuring a comprehensive understanding of the subject.  The findings indicate that public policies are instrumental in setting minimum service standards, promoting accountability and transparency, empowering communities, enhancing the professionalism of service apparatus, integrating technology into services, and enforcing compliance through penalties for providers failing to meet standards. These measures collectively contribute to significant improvements in service delivery. This research highlights the importance of policy design and implementation in fostering a responsive and efficient public service system. The findings provide actionable insights for policymakers to optimize public service frameworks and ensure community satisfaction.